RANCANG BANGUN BODI MOBIL TIPE URBAN CONCEPT BERPENUMPANG TUNGGAL DENGAN KAPASITAS MAKSIMUM 70 KG - Aditya Utama Rahmadiyanto; Susilo Adi Widyanto (JURNAL TEKNIK MESIN, 2015)
This research discuss about design and manufacture a car body of urban concept single passenger type with maximum capacity of 70 kg. The purpose of this research is to design the car body using Solidworks software, fabricate the car body that has been designed, and also to analyze the force of the car body. The designing and testing process of car body using the assist of software CAD, while the fabrication of car body using the tools and machining which provided by Manufacturing Laboratory and the result was assembled  to frame/chassis that has been made before. But, in this research the researcher underlined in manufacturing of car body. The type of car body used is composite type, which the car body separated with its chassis. The material for fabricating car body using ST 37 steel plate with thickness of 0,9 mm. The result of design is a car body with dimensions 1200 mm x 2500 mm x 1150 mm. The car body design also tested for frontal crash impact virtually with the closing speed of 56 km/h crushing a rigid barrier and resulted the value of Von Misses Stresses, Displacement, Strain and Resultant Velocity that presence the resilience of the car body that showed in enclosure in the end of this report